Impact of shipping temperature on cell viability and T cell responses to bacterial antigens [version 1; peer review: 2 approved] - Susanna J. Dunachie; Barbara Kronsteiner; Patpong Rongkard (Wellcome Open Research, 2023)
Background: Interferon-γ (IFN-γ) secretion by T cells is a key correlate of immune protection against many pathogens including tuberculosis and the neglected tropical disease melioidosis. Clinical studies in tropical regions of immune responses to pathogens and vaccine monitoring studies require the collection of samples in resource-limited rural areas and subsequent shipment to central laboratories for downstream assays and long-term storage. Here, we studied the impact of two different shipping temperatures on the viability, composition and function of peripheral blood mononuclear cells (PBMC) using multi-colour flow cytometry and IFN-g enzyme-linked immunospot assay (IFN-g ELISpot), in order to provide guidance on sample shipment conditions for future clinical studies. Methods: Paired peripheral blood mononuclear cell (PBMC) samples from recovered melioidosis patients were stored in liquid nitrogen (-196°C) and then shipped from Bangkok, Thailand to Oxford, UK at either -80°C (dry ice) or -196°C (dry shipper). After thawing, cell viability and composition were assessed by flow cytometry and antigen specific responses to Burkholderia pseudomallei (BP) were measured using IFN-g ELISpot. Results: We observed modest lowering of viability in the majority of samples and a reduction in IFN-g responses to BP which correlated to a decrease of monocytes and natural killer cells in samples shipped at -80°C compared to -196°C. Despite being lower in magnitude antigen-specific responses remained detectable in the majority of samples. Conclusions: Here we demonstrate that shipment of cryopreserved PBMC at -196°C has a benefit on cell viability, recovery and T cell responses to bacterial antigens, although useful information can still be obtained from samples shipped at -80°C, thus providing important guidance for sample management in future clinical trials.